2020
DOI: 10.3390/inorganics8060040
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Separation of Heavy Metals by Magnetic Nanostructured Beads

Abstract: This study reports the ability of magnetic alginate activated carbon (MAAC) beads to remove Cd(II), Hg(II), and Ni(II) from water in a mono-metal and ternary system. The adsorption capacity of the MAAC beads was highest in the mono-metal system. The removal efficiency of such metal ions falls in the range of 20–80% and it followed the order Cd(II) > Ni(II) > Hg(II). The model that best fitted in the ternary system was the Freundlich isotherm, while in the mono-system it was the Langmuir isotherm. The max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The number of ions adsorbed onto the beads is represented by the value K F , which is also known as the adsorption or distribution coefficient. Surface heterogeneity is represented by the value of 1/n, which becomes increasingly heterogeneous as it approaches zero [60]. One important property of the Langmuir isotherm is its ability to predict the affinity between the sorbent and adsorbate using a dimensionless quantity known as the separation factor (R L ), which has the following representation (Equation ()): 0.33emRLbadbreak=11+KLCo$$\begin{equation}\ {{\bm{R}}}_{\bm{L}} = \frac{1}{{1 + {{\bm{K}}}_{\bm{L}}{{\bm{C}}}_{\bm{o}}}}{\bm{\ }}\end{equation}$$where C o (mg/L) is the concentration of the adsorbate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of ions adsorbed onto the beads is represented by the value K F , which is also known as the adsorption or distribution coefficient. Surface heterogeneity is represented by the value of 1/n, which becomes increasingly heterogeneous as it approaches zero [60]. One important property of the Langmuir isotherm is its ability to predict the affinity between the sorbent and adsorbate using a dimensionless quantity known as the separation factor (R L ), which has the following representation (Equation ()): 0.33emRLbadbreak=11+KLCo$$\begin{equation}\ {{\bm{R}}}_{\bm{L}} = \frac{1}{{1 + {{\bm{K}}}_{\bm{L}}{{\bm{C}}}_{\bm{o}}}}{\bm{\ }}\end{equation}$$where C o (mg/L) is the concentration of the adsorbate.…”
Section: Resultsmentioning
confidence: 99%
“…One important property of the Langmuir isotherm is its ability to predict the affinity between the sorbent and adsorbate using a dimensionless quantity known as the separation factor (R L ), which has the following representation (Equation ()): 0.33emRLbadbreak=11+KLCo$$\begin{equation}\ {{\bm{R}}}_{\bm{L}} = \frac{1}{{1 + {{\bm{K}}}_{\bm{L}}{{\bm{C}}}_{\bm{o}}}}{\bm{\ }}\end{equation}$$where C o (mg/L) is the concentration of the adsorbate. For favorable adsorption, the value of R L ranges from 0 to 1, whereas for unfavorable adsorption, R L > 1, linear adsorption, and irreversible adsorption processes, R L = 1 [60]. The Langmuir and Freundlich isotherm parameters are investigated using the concentrations of 20–500 mg/L as presented in Figure 7A–D.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphology, structure, texture, and magnetic properties of nanostructured magnetic composites were studied in a previous work [ 65 ], where specific surface area and pore distribution were also explored for activated carbon composites. In addition, the particles demonstrated acceptable stability through several adsorption/desorption cycles of other contaminants.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the study reported by de Castro Alves et al [13] is focused on the production and testing of magnetic alginate activated carbon beads for the removal of heavy metals (i.e., Cd(II), Hg(II), and Ni(II)) from aqueous environments. The study investigated the effect in terms of sorption capacity over different experimental conditions (pH, recycling, and reusability) for mono-metallic systems, as well as the competitive interactions in ternary systems (thus simulating the composition of a real wastewater derived from industrial and mining effluents).…”
mentioning
confidence: 99%